You Might Be Reputable But Are You ‘‘Liked’’? Orchestrating Corporate Reputation Co-Creation on Facebook - Zarkada, Anna K.; Polydorou, Christina (My University, 2014)
Purpose — This chapter expands traditional approaches to Corporate Reputation Management by employing postmodernist approaches to value co-creation in order to identify how Facebook Features can be used to facilitate company–consumer Corporate Reputation co-creation. Methodology/approach — Using content analysis of Facebook Fan Pages, the chapter explores how 29 of the world’s most reputable corporations use Facebook Features. Findings — To a surprising degree, the corporations in the sample, despite having virtually limitless access to marketing communications resources, fail to make full use of the opportunities Facebook offers them. It appears that they have not yet fully adapted to this novel medium. Research implications — Facebook together with the locus has also shifted the focus of corporate communications from one-way company-controlled transmission of information to multiparty user-controlled conversations. Thus, Corporate Reputations can no longer be managed. Instead, by offering consumers experiences and emotional triggers, corporations can engage them into willingly marketing the corporation and its products to each other. Originality/value of chapter — This is the first systematic analysis of the practices the world’s most prominent corporations utilize (or fail to employ) on Facebook. It illustrates that companies that adapt to the Social Media ecology can successfully orchestrate customer experiences that foster the co-creation of the desired Corporate Reputation.
Keywords: Corporate Reputation; Marketing; Facebook; Content analysis; Value co-creation